Capture dynamics and control of tethered space net robot for space debris capturing in unideal capture case - Zhao, Yakun; Zhang, Fan; Huang, Panfeng (Journal of the Franklin Institute, 2020)
•The dynamic model and contact dynamic model of tethered space net robot are derived.•The contact dynamics of tethered space net robot in an unideal capture case are analyzed.•An integral version of Super-Twisting Adaptive Sliding Mode Control scheme is designed for tethered space net robot to complete the net closing action.•Natural and controlled net capture cases are simulated. Compared with the nonlinear integral sliding mode control with equivalent control technique and the original Super-Twisting algorithm, the designed control method shows a better performance to close the net in this unideal case. Tethered Space Net Robot (TSNR) is proposed as a hopeful solution for space debris capturing. An unideal case of net capture is studied in this paper, in which the net does not contact the target in the center of the net. For this case, the net cannot naturally close to wrap around the target completely after collision due to the asymmetric net configuration. Therefore, an integral adaptive Super-Twisting sliding mode control (IASTSMC) is designed to close the net. The control algorithm consists of a nonlinear integral sliding surface and adaptive Super-Twisting sliding mode control (ASTSMC), which not only has the property of “saturate the large error, magnify the small error”, but also provides a positive chattering alleviation effect. Compared with the nonlinear integral sliding mode control (ISMC) with equivalent control technique and the original Super-Twisting algorithm (STA), the proposed control method shows a better performance to close the net in this unideal case.